Energy and heat fluctuations in a temperature quench - Zannetti, Marco (2015)
Fluctuations of energy and heat are investigated during the relaxation following the instantaneous temperature quench of an extended system. Results are obtained analytically for the Gaussian model and for the large N model quenched below the critical temperature TC. The main finding is that fluctuations exceeding a critical threshold do condense. Though driven by a mechanism similar to that of Bose–Einstein condensation, this phenomenon is an out-of-equilibrium feature produced by the breaking of energy equipartition occurring in the transient regime. The dynamical nature of the transition is illustrated by phase diagrams extending in the time direction.